2020
DOI: 10.30794/pausbed.435451
|View full text |Cite
|
Sign up to set email alerts
|

Doğal Gaz Arz Güvenliği Açısından Avrupa Birliği Ülkeleri ve Türkiye Üzerine Karşılaştırmalı Bir Analiz

Abstract: Enerji arz güvenliği, enerji kaynakları açısından alıcı konumda olan ülkelerin enerji kaynakları açısından satıcı konumda olan ülkelerden dış ticaret yoluyla güvenilir, kesintisiz ve güvenli bir şekilde enerji tedarik etmesidir. Bu çalışmada, enerji arz güvenliğinin ölçülmesi amacıyla literatürde kullanılan bir takım göstergeler yardımıyla 2015 yılı için AB ülkeleri ve Türkiye'nin doğal gaz arz güvenliğinin ölçülmesi amaçlanmıştır. Doğal gaz ithalatında ülke çeşitliliği sağlama konusunda en başarılı ülkeler Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The Russia-Ukraine war that broke out in 2022 shows that natural gas supply security is an important problem not only for Turkey but also for the whole of Europe. The rate of natural gas used by Turkey in electricity generation has decreased continuously, but it has been revealed that this is not enough and should be further reduced (Birol, 2021;Konak, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Russia-Ukraine war that broke out in 2022 shows that natural gas supply security is an important problem not only for Turkey but also for the whole of Europe. The rate of natural gas used by Turkey in electricity generation has decreased continuously, but it has been revealed that this is not enough and should be further reduced (Birol, 2021;Konak, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…2018;Kaya et.al. 2018;Bağcı, 2019;Konak, 2019;Odeh & Watts, 2019, İnançlı & Akı, 2020, Obadi & Korcek, 2020, Birol, 2021, Kamacı & Akça, 2021, Halser & Paraschiv, 2022Lambert et.al. 2022;Rosa et.al.…”
Section: Introductionmentioning
confidence: 99%
“…In the study prepared by Birol (2021), it is aimed to measure the energy supply security in EU countries and Turkey according to 2015 data and to make a comparative analysis.…”
Section: Literaturementioning
confidence: 99%